Compliance with DOTS among tuberculosis patients under community based DOTS strategy in Palpa District, Nepal - Nepal, AK; Shiyalap, K; Sermsri, S; Keiwkarnka, B (International Journal of Infection and Microbiology, 2012)
INTRODUCTION: Palpa is one of the rural districts of Nepal with high incidence of tuberculosis (TB) where Community Based Directly Observed Treatment Short Course (DOTS) strategy was being trailed to make TB services accessible at community level. In spite of this, it has high defaulter rate; every year more than 5% patients had defaulted from the treatment and death due to TB was around 6%. The study, therefore, aimed to assess the patients’ compliance to the treatment and its associated factors. MATERIALS AND METHODS: A quantitative crosssectional study was carried out using structured interview schedule. All registered TB patients (n=101) who were on treatment were enrolled in the study. RESULTS: TB patients of younger age group were found to be more compliant to the treatment (p=0.02). Side effect of the drugs was the major reason for the non compliance (36.00%). More than half of the TB patients had poor knowledge on TB and its treatment. Compliance was found to be significantly associated with knowledge (p=0.02) and perception (p=0.02) of the patients towards TB. Similarly, the study showed positive association between the compliance and service accessibility (distance: p=0.00), availability of treatment supervisor (p=0.01) and health education (p=0.02). CONCLUSIONS: Patients’ compliance with the TB treatment was found to be associated with their knowledge and perception on TB and its treatment. Health education and proper counseling was deemed necessary for the patients. Service accessibility along with communication skills training to the providers including community health volunteers can increase compliance rate. DOI: http://dx.doi.org/10.3126/ijim.v1i1.6717 Int J Infect Microbiol 2012;1(1):14-19